Effects of amphetamine and caffeine on jumping behavior and brain NADH in rats - Shen Zheng; Lin Shu-Zhi (Acta Pharmacologica Sinica, 2016)
The effects of amphetamine (1.5 mg/kg ip) and caffeine (120 mg/kg ip) on jumping behavior induced by footshock in rats and on the concentrations of the reduced nicotinamide adenine dinucleotide (NADH) of brain were studied in 40 rats from the point of view about the regional brain metabolism. Amphetamine potentiated strongly the induced jumping behavior, while it increased NADH concentrations in hippocampus, cerebellum, frontal cortex, caudate nucleus and diencephalon. Caffeine increased NADH concentrations in the studied six brain structures while it potentiated the jumps in the first 3 min, but the effects of caffeine were quickly reversed. Caffeine decreased NADH concentrations in 6 brain structures and rat's jumps in the 5 th min.